Toward Elimination of Dog-Mediated Human Rabies: Experiences from Implementing a Large-scale Demonstration Project in Southern Tanzania - Mpolya, Emmanuel Abraham; Lembo, Tiziana; Lushasi, Kennedy; Mancy, Rebecca; Mbunda, Eberhard M.; Makungu, Selemani; Maziku, Matthew; Sikana, Lwitiko; Jaswant, Gurdeep; Townsend, Sunny; Meslin, François-Xavier; Abela-Ridder, Bernadette; et al. (Frontiers in Veterinary Science, 2017)
A rabies elimination demonstration project was implemented in Tanzania from 2010 through to 2015, bringing together government ministries from the health and veterinary sectors, the World Health Organization (WHO), and national and international research institutions. Detailed data on mass dog vaccination campaigns, bite exposures, use of post-exposure prophylaxis (PEP) and human rabies deaths were collected throughout the project duration and project areas. Despite no previous experience in dog vaccination within the project areas, district veterinary officers were able to implement district-wide vaccination campaigns that for most part progressively increased the numbers of dogs vaccinated with each phase of the project. Bite exposures declined, particularly in the southernmost districts with the smallest dog populations, and health workers successfully transitioned from primarily intramuscular (IM) administration of PEP to intradermal (ID) administration, resulting in major cost savings. However, even with improved PEP provision, vaccine shortages still occurred in some districts. In laboratory diagnosis, there were several logistical challenges in sample handling and submission but compared to the situation before the project started there was a moderate increase in the number of laboratory samples submitted and tested for rabies in the project areas with a decrease in the proportion of rabies-positive samples over time. The project had a major impact on public health policy and practice with the formation of a One-Health Coordination Unit at the Prime Minister’s Office and development of the Tanzania National Rabies Control Strategy, which lays a roadmap for elimination of rabies in Tanzania by 2030 by following the Stepwise Approach towards Rabies Elimination (SARE). Overall, the project generated many important lessons relevant to rabies prevention and control in particular and disease surveillance in general. Lessons include the need for (1) a specific unit in the government for managing disease surveillance, (2) application of innovative data collection and management approaches such as the use of mobile phones; (3) close cooperation and effective communication amongst all key sectors and stakeholders; and (4) flexible and adaptive programmes that can incorporate new information to improve their delivery, and overcome challenges of logistics and procurement.